BUILDING VOCABULARY: USING THE THESAURUS AND DICTIONARY EFFECTIVELY - Haqberdiyeva Barchinoy,; Ravshan Khujakulov, (TADQIQOTLAR, 2026)
A  rich  and  precise  vocabulary  is  essential  for  effective  communication  in academic discourse. This article will discuss the roles that the dictionary and thesaurus play in expanding and refining vocabulary. The dictionary acts as the chief determinant of the denotative meaning, giving foundational knowledge through elaborate entries and contextual examples (Nation, 2001), while the thesaurus allows for stylistic nuance and lexical variation. Central to this thesis is Khujakulov's (2024) argument for using these  resources  in  concert  with  one  another  to  understand  more  appropriately  the nuances of word choice to navigate complexities of choosing words that best align with both the intended meaning and appropriate connotation of the synonyms considered (Cruse, 2000). The article continues to mention the most common pitfalls in dealing with  synonyms,  including  indiscriminate  synonym  substitution,  and  describes  a strategy to build a productive and robust vocabulary through continued exposure and active use. Through mastering the effective use of such resources, one finds their way to present involved ideas clearly, confidently, and poignantly.